Sign of the Times: The Framing of Computational Thinking in Danish, Finnish, and Norwegian Curricula - Pajchel, Katarina; Mifsud, Louise; Frågåt, Thomas; Rehder, Mads Middelboe; Juuti, Kalle; Bogar, Yurdagül; Lavonen, Jari; Schrøder, Vibeke; Aalbergsjø, Siv G.; Rognes, André (Nordic Journal of Comparative and International Education (NJCIE), 2024)
This paper discusses the significance of school curricula in reflecting societal priorities and needs, focusing on the incorporation of computational thinking (CT) in Nordic national curricula. Our point of departure is that the preparedness of future generations for a digitally driven society can be determined by analysing how CT is either explicitly or implicitly framed in school curricula. Accordingly, this study examined the school curricula of Denmark, Finland, and Norway in terms of their similarities and differences in how they framed CT, as these countries have different approaches to the inclusion of CT. A framework for analysis that was grounded in influential works on CT in education was developed, focusing on problem-solving, algorithmic and transversal practices. National-level curricula were examined using a content analysis. Despite the differences in the approaches used in these countries, our findings indicate similarities across all three curricula, with an emphasis on how CT was framed.